Systemic lupus erythematous and clinical outcomes in peritoneal dialysis - Proenca de Moraes, T.; Massignan, B.; Figueiredo, A. E.; Barretti, P. [UNESP]; Olandoski, M.; Kirk, A.; Pecoits-Filho, R. (Sage Publications Ltd, 2015)
Background: The prevalence of systemic lupus erythematous (SLE) patients requiring renal replacement therapy (RRT) is increasing but data on clinical outcomes are scarce. Interestingly, data on technique failure and peritoneal-dialysis (PD)-related infections are rarer, despite SLE patients being considered at high risk for infections. The aim of our study is to compare clinical outcomes of SLE patients on PD in a large PD cohort. Methods: We conducted a nationwide prospective observational study from the BRAZPD II cohort. For this study we identified all patients on PD for greater than 90 days. Within that subset, all those with SLE as primary renal disease were matched with PD patients without SLE for comparison of clinical outcomes, namely: patient mortality, technique survival and time to first peritonitis, then were analyzed taking into account the presence of competing risks. Results: Out of a total of 9907 patients, we identified 102 SLE patients incident in PD and with more than 90 days on PD. After matching the groups consisted of 92 patients with SLE and 340 matched controls. Mean age was 46.9 +/- 16.8 years, 77.3% were females and 58.1% were Caucasians. After adjustments SLE sub-hazard distribution ratio for mortality was 1.06 (CI 95% 0.55-2.05), for technique failure was 1.01 (CI 95% 0.54-1.91) and for time to first peritonitis episode was 1.40 (CI 95% 0.92-2.11). The probability for occurrence of competing risks in all three outcomes was similar between groups. Conclusion: PD therapy was shown to be a safe and equally successful therapy for SLE patients compared to matched non-SLE patients.
Keywords: Lupus; Peritoneal dialysis; BRAZPD; Mortality; Peritonitis; Technique failure